The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1063/1.1828580
|View full text |Cite
|
Sign up to set email alerts
|

High-sheet-charge–carrier-density AlInN∕GaN field-effect transistors on Si(111)

Abstract: Al In N ∕ Ga N heterostructures have been proposed to possess advantageous properties for field-effect transistors (FETs) over AlGaN∕GaN [Kuzmík, IEEE Electron Device Lett. 22, 501 (2001); Yamaguchi et al., Phys. Status Solidi A 188, 895 (2001)]. A major advantage of such structures is that AlInN can be grown lattice-matched to GaN while still inducing high charge carrier densities at the heterointerface of around 2.7×1013cm−3 by the differences in spontaneous polarization. Additionally, it offers a higher ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(73 citation statements)
references
References 19 publications
5
67
1
Order By: Relevance
“…On the other hand, InN can only be grown at low temperatures and high ammonia partial pressures, whereby high ammonia partial pressures have also a strong effect on the AlN growth rate. However, these problems have been widely overcome in first promising experiments [8][9][10][11]. In particular, it has been found that the insertion of an optimized AlN interlayer reduces the alloy related interface roughness and improves therefore the electron mobility dramatically as shown in Fig.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…On the other hand, InN can only be grown at low temperatures and high ammonia partial pressures, whereby high ammonia partial pressures have also a strong effect on the AlN growth rate. However, these problems have been widely overcome in first promising experiments [8][9][10][11]. In particular, it has been found that the insertion of an optimized AlN interlayer reduces the alloy related interface roughness and improves therefore the electron mobility dramatically as shown in Fig.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…10 Regardless of the final application, investigations on both the electrical and optical properties of the 2DEG are crucial for understanding the intrinsic properties of the InAlN/GaN heterostructures, which is the bottleneck to advance the nitride electronics technology. Up to now, InAlN/GaN HS have been studied widely by electrical measurements, 5,11 however, there is still a lack of systematic studies concerning optical characterization.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Despite their potential applications in electronic and optical devices, the fabrication of high quality lattice-matched InAlN epitaxial layers on GaN remains challenging task irrespective of employing sophisticated epitaxial deposition methods such as molecular beam epitaxy (MBE) and metal-organic chemical vapor deposition (MOCVD). The spinodal phase separation and composition inhomogeneity due to the large thermodynamic miscibility gap caused by the large difference of covalent bond length between AlN and InN makes it difficult in alloying at optimum growth temperature.…”
Section: Introductionmentioning
confidence: 99%